2010
DOI: 10.1271/bbb.90924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tetrahydropterines on the Generation of Quinones Catalyzed by Tyrosinase

Abstract: Tetrahydrobiopterine (6BH 4 ) can diminish the oxidative stress undergone by keratinocytes and melanocytes by reducing the o-quinones generated by the oxidation of the corresponding o-diphenols. We found that 6BH 4 and their analogs reduced all the o-quinones studied. The formal potentials of different quinone/ diphenol pairs indicate that the o-quinones with withdrawing groups are more potent oxidants than those with donating groups.Key words: tetrahydropterines; quinones; o-diphenols;voltammograms; tyrosinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…3). The HHQ derivative that is generated in the passage from EoxHQ to EmHHQ, when released, is oxidized by the oxygen in the medium [38].…”
Section: Deviations Of the Kinetic Mechanism For Monophenolase Activi...mentioning
confidence: 99%
See 3 more Smart Citations
“…3). The HHQ derivative that is generated in the passage from EoxHQ to EmHHQ, when released, is oxidized by the oxygen in the medium [38].…”
Section: Deviations Of the Kinetic Mechanism For Monophenolase Activi...mentioning
confidence: 99%
“…however, years later it was proposed that it was not a substrate for the enzyme [40]. Later it was clearly demonstrated that HQ is a tyrosinase substrate in the presence of hydrogen peroxide, ascorbic acid and with catalytic amounts of TBC [38,41]. This property of HQ may be the origin of its adverse effects, although it has been widely used as a depigmenting agent [42].…”
Section: Enzymatic Action Of Tyrosinase On Hydroquinone Substrates Ty...mentioning
confidence: 99%
See 2 more Smart Citations
“…The product of the action of TYR on L-tyrosine and L-DOPA (the o-dopaquinone) acts as an oxidant of NADH, since the redox potentials are o-quinone/diphenol = 0.152 V, NAD þ =NADH þ H þ ¼ À0:315 V. 22) This was observed when both TYR activities (diphenolase and monophenolase) were studied in the presence of NADH.…”
Section: Nadh Effect On Melanogenesis Under Aerobic Conditionsmentioning
confidence: 99%